STUDI PERBANDINGAN TENTANG REGULASI PERSAINGAN USAHA DI INDONESIA DENGAN ANTITRUST LAW DI AMERIKA. - Atmanto , Dwi; Dewi , Retno Sari (Gapenas Publisher, 2025)
Competition Law plays an important role in economic life in terms of business competition. This article compares competition law in Indonesia with competition law in the United States using a comparative study approach with a normative legal method based on legal documents and primary literature. Based on the findings of comparative research on competition law in Indonesia with competition law in the United States, it was found that there are differences in historical background, legal system and economic structure which resulted in the birth of different approaches in regulating and enforcing competition law. The purpose of this article is to provide a comprehensive understanding of the differences in the concept of legal rules on competition in Indonesia with competition in the United States.